"Sincerely Held Principles" or Prejudice? The Tennessee Counseling Discrimination Law. (February 2020) - Grzanka, Patrick R.; Spengler, Elliot S.; Miles, Joseph R.; Frantell, Keri A.; DeVore, Elliott N.
In 2016, Tennessee became the first state to allow counselors and therapists in private practice to deny services to any client based on the therapist's sincerely held principles . The law's proponents framed mental health care ethics as infringing on counselors' religious liberties; its critics denounced the bill because it apparently targeted LGBT+ individuals. This exploratory study is the first statewide assessment of LGBT+ Tennesseans' ( N = 346) perceptions of the law and how it may affect their help-seeking attitudes and behaviors. Evidence suggests widespread awareness of the law among our respondents and deep skepticism toward mental health care. Further, most respondents view the law as cover for discrimination. We stress the need for broader research on conscience clauses and call for advocacy against these laws, which have the potential to engender widespread harm to multiple minority groups.